Nilai Kearifan Lokal pada Implementasi Komunikasi Antarbudaya terhadap dalam Tradisi Perang Topat di Lingsar Lombok Barat - Acim, Subhan Abdullah; yaqinah, siti nurul (LENTERA, 2019)
The tradition of Topat War is one of Lombok's very valuable cultural assets that is held annually. Not only that this tradition have deep meaning to people in Lombok, it is also Topat Warevidence of the Lombok people's spirit to the preserve their culture.. Therefore, the purpose of this study is to investigate the process of implementing the values of local wisdom in the tradition of Topat War in Lingsar and the implementation of intercultural communication in the tradition of Topat War. In this study, a descriptive-qualitative method is applied to analyze data obtained through interviews, observations and documentation.. Findings reveal that the process of implementing the values of local wisdom in the Topat War tradition is carried out in several stages which include preparation, preliminary ceremonies and the peak of the Topat War event which coincides with the Sasak Calendar, where activities begin in the morning, ending with the Beteteh ceremony which is the closing of the whole series of events. The values of local wisdom contained in the Topat War tradition, including the value of togetherness, the value of tolerance and religious values. The implementation of intercultural communication in the Topat War tradition is done through group communication both verbally and nonverbally. Forms of verbal communication are manifested in the form of deliberation and interpersonal communication while non-verbal communication is manifested in forms such as dance, performance, prayer and throwing each other topats. This intercultural communication serves as a binding mechanism among all parties involved in the Topat War tradition.Â Keywords: Â Intercultural Communication, Local Wisdom Values, and Perang Topat.Â